2010
DOI: 10.1002/jbm.a.32803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of orthopedic polymer particles on chemotaxis of macrophages and mesenchymal stem cells

Abstract: Wear particles generated from total joint arthroplasty (TJA) stimulate macrophages to release chemokines. The role of chemokines released from wear particle-stimulated macrophages on the migration of macrophages and osteoprogenitor cells in vitro has not been elucidated. In this study, we challenged murine macrophages (RAW 264.7) with clinically relevant polymethyl methacrylate (PMMA, 1-10 μm) and ultra high molecular weight polyethylene (UHMWPE, 2-3 μm) particles. The chemotactic effects of the conditioned me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 30 publications
(38 reference statements)
0
46
0
Order By: Relevance
“…The methodology for the chemotaxis experiments reported herein were originally developed and reported by Huang et al 14 from our laboratory. In the migration experiments, human macrophages were used as the migrating cells due to their high sensitivity to chemotactic cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology for the chemotaxis experiments reported herein were originally developed and reported by Huang et al 14 from our laboratory. In the migration experiments, human macrophages were used as the migrating cells due to their high sensitivity to chemotactic cytokines.…”
Section: Methodsmentioning
confidence: 99%
“…To this end, it has recently been shown that polymethyl methacrylate particle-conditioned media induced migration of MSCs, an effect that was blocked by neutralizing the macrophage inflammatory protein-1a (MIP-1a), a chemokine also known to attract monocyte/macrophages. 17 These preliminary results suggest that some of the same chemokines that recruit circulating monocytes/macrophages could also recruit osteoprogenitor cells.…”
mentioning
confidence: 90%
“…Endothelial cells recruit circulating cells, as monocytes 8.1 Infl ammatory process activated by polymeric debris and mediated by macrophages, leading to soft tissue damage and bone resorption. and lymphocytes, through a chemo-attractive mechanism mediated by MCP-1, MIP-1 and IL-8, to their surface: these cells roll along the endothelial cells, to extravasate and reach the reactive site (Huang et al , 2010). In addition to monocytes, lymphocytes have been shown to differentiate into osteoclasts (Roato et al , 2010).…”
Section: Biological Reactions To Orthopaedic Implant Degradation Prodmentioning
confidence: 99%